1990
DOI: 10.1016/0020-7292(90)90653-3
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐biological factors influencing infertility in a rural Nigerian community

Abstract: An assessment of factors influencing infertility in a rural Nigerian community revealed a prevalence rate of 12.9% primary infertility. Secondary infertility among the subjects was 54.1%. Age, education and religion of respondents had statistically significant influence on infertility (P less than 0.05) but not income (P greater than 0.05). The correlation between age of respondents and infertility was statistically significant (P less than 0.05). Primary health care efforts aimed at implementing maternal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia (Sundby et al ., 1998) and 11.8% in Ghana (Geelhoed et al ., 2002) compared with 21.2% in northwestern Ethiopia (Haile, 1990) and between 20 and 30% in Nigeria (Ebomoyi and Adetoro, 1990; Adetoro and Ebomyi, 1991; Okonofua, 1996; Larsen, 2000). Even less data are available from Asia and Latin-America, but a report compiled by the World Health Organization (WHO) indicated that the prevalence of infertility in these regions fell within the globally expected range 8–12% of couples of reproductive age and was thus lower when compared with African countries (World Health Organization, 1991).…”
Section: Prevalence Of Infertility In Developing Countriesmentioning
confidence: 96%
“…In sub-Saharan Africa, the prevalence differs widely from 9% in the Gambia (Sundby et al ., 1998) and 11.8% in Ghana (Geelhoed et al ., 2002) compared with 21.2% in northwestern Ethiopia (Haile, 1990) and between 20 and 30% in Nigeria (Ebomoyi and Adetoro, 1990; Adetoro and Ebomyi, 1991; Okonofua, 1996; Larsen, 2000). Even less data are available from Asia and Latin-America, but a report compiled by the World Health Organization (WHO) indicated that the prevalence of infertility in these regions fell within the globally expected range 8–12% of couples of reproductive age and was thus lower when compared with African countries (World Health Organization, 1991).…”
Section: Prevalence Of Infertility In Developing Countriesmentioning
confidence: 96%
“…[5] In sub-Saharan Africa, the prevalence differs widely from 9% in Gambia to 11.8% in Ghana compared with 21.2% in northwestern Ethiopia and between 20% and 30% in Nigeria. [67891011] There is paucity of data from countries of Asia to Latin America. According to the WHO, the prevalence of infertility in these regions is between 8% and 12% in couples of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Hence the psychological impact associated with infertility is likely to be greater in developing countries. 3,7 Existing literature suggests poor marital adjustment and quality of life in women with infertility as compared to normal couple. 8 Studies report a revisit of choice of spouse selection and constant attribution of spouse as a reason for infertility among couple when they undergo stress.…”
Section: Introductionmentioning
confidence: 99%